Kulturpolitiske kanonkugler - Reestorff, Camilla Møhring (K&K - Kultur og Klasse, 2007)
Kulturkanonen og kulturens nationalstatslige forankring The Cultural Canon and the national anchoring of culture This paper deals with the importance of the concepts of culture and class in contemporary Danish politics. The concepts are necessary in order to understand the political discourse about globalisation and the ways in which the relations between the local and the global are changing. The Ministry of Culture’s Canon of Culture, launched on the 24th of January 2006, exemplifies how the government’s conception of globalisation as a threat to the nation results in a cultural political strategy, which is an attempt to establish a shared national comprehension of culture as locally bound. It is claimed that culture is used as a means to establish an imagined, territorially bound and unchangeable nation state. The local anchoring of culture entails that trans-national and global communities based on culture and class are undermined in favour of national identity. The complexity of the nation and the world is reduced because of the national standardisation of culture, which installs an illusory order, a community based on values and culture. Culture becomes hierarchical – this article says – when those who are not a part of the community are excluded. Human beings, societies and cultures are then divided.